A Collaborative Governance Perspective in Ecotourism Development in Ujung Kulon National Park, Banten-Indonesia - Kurniawan, Bambang; Rahmatunissa, Mudiyati; Utami, Sawitri Budi; Buchari, Rd Ahmad (Journal of Ecohumanism, 2024)
This research aims to examine ecotourism activities in Ujung Kulon National Park, Pandeglang Regency, Banten-Indonesia. This research uses qualitative methods, with a comprehensive case study approach. The focus of the research is on collaborative governance in the development of ecotourism in Ujung Kulon National Park. This research also pays attention to the various dimensions of the roles and functions of the actors involved since the starting condition phase, institutional design, facilitative leadership, and collaborative process (Ansell and Gash, 2008). Data collection techniques were carried out through observation, in-depth interviews with informants, literature studies, and tracking news in the mass media. Data and information were obtained through several sources of informants including: 1) actors of ecotourism activities such as the government (Ujung Kulon National Park and Pandeglang Regency Government), 2) local communities, 3) non-governmental organizations, and 4) the private sector as service providers. The results of the study found that collaborative governance as a model of cooperation for ecotourism activities in Ujung Kulon National Park Pandeglang Banten has been carried out, although there are still many obstacles and challenges. This can be seen in the implementation of citizen participation in the activity planning stage, several obstacles such as the inequality of knowledge of community members in understanding the concept of nature conservation and the concept of ecotourism, then the earthquake, the covid19 pandemic outbreak, and the central role of the Ujung Kulon National Park office. Collaborative Governance as a concept always refers to efforts to realize consensus and active participation from the stakeholders involved, as well as interdependence and common interests being factors that cannot be ignored.